Bicarbonate supplementation enhanced biofuel production potential as well as nutritional stress mitigation in the microalgae Scenedesmus sp. CCNM 1077. (October 2015) - Pancha, Imran; Chokshi, Kaumeel; Ghosh, Tonmoy; Paliwal, Chetan; Maurya, Rahulkumar; Mishra, Sandhya
Highlights: Bicarbonate additions enhance biomass and biochemical content of microalgae. 0.6 g/L was optimum bicarbonate concentration. Bicarbonate supplementation helps in nutritional stress ameroliation in microalgae. Nitrate starvation with bicarbonate addition produced highest carbohydrate and lipid. Scenedesmus sp. is a potential feedstock for biodiesel and bioethanol production. Abstract: The aim of the present study was to find out the optimum sodium bicarbonate concentration to produce higher biomass with higher lipid and carbohydrate contents in microalgae Scenedesmus sp. CCNM 1077. The role of bicarbonate supplementation under different nutritional starvation conditions was also evaluated. The results clearly indicate that 0.6 g/L sodium bicarbonate was optimum concentration resulting in 20.91% total lipid and 25.56% carbohydrate along with 23% increase in biomass production compared to normal growth condition. Addition of sodium bicarbonate increased the activity of nutrient assimilatory enzymes, biomass, lipid and carbohydrate contents under different nutritional starvation conditions. Nitrogen starvation with bicarbonate supplementation resulted in 54.03% carbohydrate and 34.44% total lipid content in microalgae Scenedesmus sp. CCNM 1077. These findings show application of bicarbonate grown microalgae Scenedesmus sp. CCNM 1077 as a promising feedstock for biodiesel and bioethanol production.